Update - the development of the Eastern Caribbean Securities Exchange (2000)
Presents the activities included in completing Phase 2 - Analysis and design by the consulting teams - The Intrados Consulting Group and the Aries Group Ltd. Outlines the commitments from the consultants for work out standing - Phase 3 & 4 for the period December 1999 - March 2000.
Keywords: FINANCIAL MARKET